Evaluation of urine cultures obtained by cystocentesis from cats with urethral obstruction at the time of hospital admission and after urethral catheterization - G.C. Schaefer; F.V.A. da Costa; S.F. Valle; V.C. Matesco; J.W. Heck; A. Spanamberg; L. Ferreiro; F.H.D. Gonzalez (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2023)
ABSTRACT The aims of this study were to search for the presence of bacterial and fungal growth in urine samples from cats with urethral obstruction, to identify the causative infectious agents, and to compare select clinical-laboratory parameters with urine culture results after urethral catheterization. Twenty-eight male cats were enrolled in this prospective study. Urethral catheterization was performed aseptically, and the catheter was maintained for 24-48 hours with a sterile closed collection system. No antibiotics were used during this period. The first urine sample was obtained at the time of presentation, and the second, 24-48 hours after catheter removal, both by cystocentesis. Two cats (7.1%) presented a positive bacterial urine culture on the first sample. The frequency of positive urine cultures in the second sample was 52.4% (11/21 cats). One third of bacterial pathogens were Gram-positive, one third were Gram-negative, and one third were mixed isolates. Fungal cultures were all negative. There was significant association of positive urine culture results with pyuria (P=0.0128). A high frequency of positive urine cultures after urinary catheter removal was observed, despite respecting the standards of care for urethral catheters. Still, these results should be interpreted with caution, since intermittent bladder flushing was performed disconnecting the collecting system, which may have represented a critical point for bacterial contamination. It is emphasized that urine cultures should be considered as follow up in cats with urethral obstruction, after urethral catheter removal.